Evaluation of Laminate Veneer Preparation Depth with 3D Systems - Orhan Öztoprak; Yılmaz Umut Aslan; Yasemin Özkan (Selçuk University, 2020)
Background:Preparation depth of laminate veneers are essential in retention and structural integrity of restorations. The aim of this study was to evaluate the difference between a trained professional prosthodontist (PP) and a postgraduate prosthodontics student (PPS) in the preparation depth of laminate veneers by scanning the tooth with a 3D scanner before and after the preparation. Methods: Twenty extracted human maxillary central incisors were evaluated by a PP and PPS. A 0.5 mm depth guide bur was used in for facial reduction and a 1 mm incisal reduction was performed with a deep chamfer. The teeth were scanned with a laser scanner at an accuracy of 10 µm.The teeth were separated into 3 parts (incisal, middle and cervical) and then 5 points were randomly selected on the unprepared tooth and then lapped over when the preparation had been completed. The data of the difference was calculated in 3D scanning software Magics (Materialise NV, Belgium).Statistical analysis were performed with one-way ANOVA (p < 0.05).Results: PP results showed mean values in the Incisal of 0.328+0.045 mm, Middle of 0.375+0.097 mm and Cervical of 0.471+0.07 mm. PPS results showed mean values in the Incisal of 0.323+0.056 mm, Middle results of 0.403+0.083 mm and Cervical results of 0.462+0.075 mm.Conclusion: These results suggest that a PP or a PPS can both achieve the same precision in there preparation using a depth guide bur. Key Words: Ceramic laminate veneer preperation, 3D scanning, depth guide bur.